Patient Experiences, Trust, and Preferences for Health Data Sharing. Issue 3 (March 2022) - Jones, Rochelle D.; Krenz, Chris; Griffith, Kent A.; Spence, Rebecca; Bradbury, Angela R.; De Vries, Raymond; Hawley, Sarah T.; Zon, Robin; Bolte, Sage; Sadeghi, Navid; Schilsky, Richard L.; Jagsi, Reshma
Abstract : PURPOSE: Scholars have examined patients' attitudes toward secondary use of routinely collected clinical data for research and quality improvement. Evidence suggests that trust in health care organizations and physicians is critical. Less is known about experiences that shape trust and how they influence data sharing preferences. MATERIALS AND METHODS: To explore learning health care system (LHS) ethics, democratic deliberations were hosted from June 2017 to May 2018. A total of 217 patients with cancer participated in facilitated group discussion. Transcripts were coded independently. Finalized codes were organized into themes using interpretive description and thematic analysis. Two previous analyses reported on patient preferences for consent and data use; this final analysis focuses on the influence of personal lived experiences of the health care system, including interactions with providers and insurers, on trust and preferences for data sharing. RESULTS: Qualitative analysis identified four domains of patients' lived experiences raised in the context of the policy discussions: (1) the quality of care received, (2) the impact of health care costs, (3) the transparency and communication displayed by a provider or an insurer to the patient, and (4) the extent to which care coordination was hindered or facilitated by the interchange between a provider and an insurer. Patients discussed their trust in health care decision makers and their opinions about LHS data sharing. CONCLUSION: Additional resources, infrastructure, regulations, and practice innovations are needed to improve patients' experiences with and trust in the health care system. Those who seek to build LHSs may also need to consider improvement in other aspects of care delivery.